(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Mauryan Empire, one of the largest and most influential empires in ancient India, implemented a highly structured and centralized economic policy that played a pivotal role in its success. The economic framework of the Mauryan state, under rulers like Chandragupta Maurya and Ashoka, was designed to manage vast resources and ensure prosperity across its vast territories. This analysis delves into the empire’s core economic strategies, which included an agrarian-based economy, comprehensive trade networks, efficient taxation systems, and large-scale infrastructure projects. At the heart of the Mauryan economy was agriculture, which served as the primary source of revenue. The state regulated agricultural production and imposed taxes on farmers, ensuring a steady income for the empire. Infrastructure investments, such as irrigation systems and roads, were central to improving agricultural productivity and facilitating trade. The Mauryan rulers also established a standardized currency system, which facilitated commerce both within the empire and with foreign regions, boosting economic activity and trade.